Comparative study of DNA and RNA extraction methods for high-quality nucleic acid isolation from Cullenia exarillata A. Robyns: DNA and RNA extraction from C. exarillata - S., Revathy; K. K., Sabu; S., Anilkumar (Cellular and Molecular Biology, 2025)
Isolation of high-quality DNA and RNA from plants with high polysaccharide and secondary metabolite content is typically difficult, particularly in the case of trees. Metabolites commonly undergo co-precipitation with RNA and DNA, resulting in degradation of their quality. Cullenia exarillata leaf samples were subjected to various DNA and RNA extraction techniques, and the resulting data were compared and analysed. The isolation of high-quality DNA and RNA is crucial for the advancement of molecular and biotechnological techniques that aim to preserve the endemic status of C. exarillata and this research is to establish an efficient procedure for extracting DNA and RNA from C. exarillata. This method will make molecular and genomic research easier in forestry and conservation fields. In this research, we evaluated various methods for extracting high quality DNA and total RNA from C. exarillata tree, incorporating minor modifications in standard procedure. To acquire DNA and RNA of superior quality, a comparison was made between conventional DNA and RNA extraction methods and a variety of commercial kits thatrevealed the conventional technique yielded DNA samples of superior purity and concentration. It was discovered that combining modified commercial and conventional procedures yielded RNA with exceptionally high concentration and purity. The Agilent 2100 Bioanalyzer and NanoDrop spectrophotometer ensure the impeccable purity of the nucleic acids generated via these procedures. Additionally, the application of agarose gel electrophoresis unveiled unique bands. Further investigation was conducted to validate the purity and amplification of the DNA and RNA that were collected. This study clarifies a method for extracting sufficient and high-quality amounts of DNA and RNA from C. exarillata; future research on this plant will greatly benefit from knowing this information.